Triple band notched microstrip antenna using planar series 2x2 element array for 5G communication system - Surjati, Indra; Alam, Syah; Sari, Lydia; Hilyawan, Muhammad Reynaldhy; Zakaria, Zahriladha; Shairi, Noor Azwan; Hikmaturokhman, Alfin; Firmansyah, Teguh (Sumy State University, 2022)
This research proposes the design of a wideband microstrip antenna with triple notch bands for the fifth generation (5G) communication system. The antenna is designed using FR-4 substrate with εr of 4.3, tanδ of 0.0265 and a thickness of 1.6 mm. Triple notch bands are generated using a 2×2 element array configuration that connects each patch antenna in series and is arranged horizontally. From the simulation results, a triple band notched antenna is obtained with a resonant frequency of 3.15, 3.32 and 3.72 GHz. The fractional bandwidth (FBW) of the proposed antenna is 770 MHz or 22 % and the gain is 9.24 dB with an operating frequency of 3.5 GHz. The proposed antenna succeeded in increasing the bandwidth and gain up to 285 % and 55 %, respectively, compared to a single element antenna. The studied antenna design can be recommended as it is also very useful as a receiving antenna for the 5G communication system.